A new global potential energy surface of the SH2+(X4A′′) system and quantum calculations for the S+ + H2(v = 0–3, j = 0) reaction. Issue 8 (18th February 2021) - Zhu, Ziliang; Zhang, Aijie; He, Di; Li, Wentao
Abstract : A new global potential energy surface (PES) for the ground state of the SH2 + (X 4 A′′) system is constructed using a permutation invariant polynomial neural network method. Abstract : A new global potential energy surface (PES) for the ground state of the SH2 + (X 4 A′′) system is constructed using a permutation invariant polynomial neural network method. In ab initio calculations, the MRCI-F12 method with the AVTZ basis set is used. Furthermore, the dynamics calculations of the S + + H2 ( v = 0–3, j = 0) → SH + + H reaction are carried out based on the new PES. The reaction probabilities and integral cross sections are compared with available theoretical calculations. Present values are in general good agreement with the previous theoretical studies. However, some discrepancies can still be found due to different PESs used in the calculation. Furthermore, the vibrational energy of the reactant molecule can significantly enhance the reactivity compared to the translational energy. The differential cross sections indicated that the reaction mechanism is changed from the "head-on" rebound mechanism to the tripping mechanism with the increasing number of initial vibrational excitation state.